IMPLEMENTASI KEBIJAKAN PENDIDIKAN DALAM KONDISI VUCA - Sitiriwanti, Misnar; Sartima, Tarma; Khairul, Khairul; Fadhlan, Fadhlan; Krisnawansyah, Yahya; Andrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The education sector was among the sectors most affected by the non-natural disaster of the COVID-19 pandemic. During this period, educational policies underwent a major transformation, shifting from conventional face-to-face instruction to fully online distance learning. Policymakers and education stakeholders experienced multiple stages of policy implementation, often accompanied by policy adjustments and revisions. Interactions among stakeholders, which had previously involved primarily the Education Office and schools, expanded to include parents as active participants in supporting learning at home. Consequently, the policy network became broader than that typically observed in public policy implementation. This study aims to explain the factors contributing to the successful implementation of education policy during the COVID-19 pandemic in Agam Regency. A qualitative approach was employed using data collected through interviews and document analysis, including the COVID-19 daily records published on the Agam Media Center website. The findings reveal that the successful implementation of education policy during the COVID-19 pandemic was influenced by four factors proposed by George Edward III: (1) effective policy communication, characterized by the rapid and accurate transmission of policy information among implementers through online communication platforms and limited face-to-face meetings; (2) adequate policy resources, including regional government budget allocations (APBD), facilities, and infrastructure adapted to health protocols, as well as coordinated human resources through the Agam Regency COVID-19 Task Force; (3) democratic attitudes, openness, and cooperative behavior among implementing actors; and (4) a well-defined bureaucratic structure and strong interagency coordination supported by clear Standard Operating Procedures (SOPs). The success of policy implementation was further strengthened by intensive coordination and interaction among government agencies, schools, community groups, and parents in supporting students' learning at home.